A Contrastive Analysis of the Production of English and Yoruba Vowels by Yoruba-English Bilingual Students in University of Nigeria, Nsukka (Global Journal of Human-Social Science, 2021)
This study examined the production of English vowels by Yoruba-English bilingual undergraduate students at the University of Nigeria, Nsukka. The instrument used for data collection was the pronunciation of a prepared word list. Sixty (60) students who speak Yoruba as their first language were randomly selected from five departments. The bilingual status of the students made it possible to assemble a corpus which reveals their various levels of competency in English. The result of the findings indicate that Yoruba language vowels differ to a large extent from English language and due to this, there are certain variations and deviations in the realization of English vowels by Yoruba-English bilingual students. From the data gathered, analysis shows that we do not have an equal number of vowels in both languages and there are some vowels in Yoruba that are not present in the English language.
Keywords: contrastive analysis; vowels; english; yoruba; students